Innovation and external knowledge sources in knowledge intensive business services (KIBS): evidence from de-industrialized UK regions. Issue 9 (19th October 2020) - Savic, Maja; Lawton Smith, Helen; Bournakis, Ioannis
ABSTRACT: This paper explores the effect of external knowledge sources and the uneven geography on innovation activity in small Knowledge Intensive Business Services (KIBS). It draws on results from a survey of 342 small and medium (SME) KIBS located in the UK's North East and West Midlands, both de-industrialized regions. It is shown that innovation is supported by knowledge gained from frequent interaction with customers both regional and UK based as well as international. More frequent interaction with local business networks, informal contacts and national licencing arrangements also enhances innovativeness. Various industry-specific business networks and regional government agencies act as important sources of knowledge and networking and these are more important for KIBS located in the North East. The results indicate that more frequent collaboration with regional universities and regional public sector organizations does not benefit KIBS from either region. Also, while we acknowledge a positive effect of R&D on KIBS innovativeness we argue that its effect is less important compared to regional and extra regional knowledge sources.